The Synergy Between Islam and The Local Culture of Maluku, Indonesia - Dortje Leonora Yokbeth Lopulalan; Selvianus Salakay; Makmur Harun (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
The cultural context of the Maluku archipelago is greatly influenced by Islam, which profoundly impacts the way of life of its diverse communities. Religion exists alongside and interacts with society's social dynamics while incorporating specific cultural values. This study aims to analyze and gain insight into the distinct concept of Islam in Maluku as it undergoes continuous development in conjunction with the local culture. A qualitative research approach is employed, specifically focusing on emic perspectives.  Priority is given to the views and interpretations of local informants. Moreover, the ideation process is enhanced by incorporating literature studies; efforts to conceptualize the ideas in this writing were enriched by using qualitative research methods, selected data sources, and prioritizing the emic perspective. The informants' views were prioritized in terms of how they view and interpret the world from their perspective, together with literature studies and various references related to the topic. The study findings indicate that Islam has experienced growth and evolution in Maluku as a religion, resulting in its interaction with diverse local cultures. The culture of the Moluccans has changed over time, originating in their early settlement. This has resulted in forming a community that has developed its distinct values, which revolve around human relationships and the environment. Islam offers a logical reasoning for preserving Moluccan culture, promoting peaceful coexistence among the people of Maluku, and serving as an example of socio-religious integration.